An evaluation of a punisher assessment for decreasing automatically reinforced problem behavior. Issue 1 (20th September 2018) - Verriden, Amanda L.; Roscoe, Eileen M.
Abstract : We extended research on the identification and evaluation of potential punishers for decreasing automatically reinforced problem behavior in four individuals with autism spectrum disorder. A punisher selection interview was conducted with lead clinicians to identify socially acceptable punishers. During the treatment evaluation, treatment phases were introduced sequentially and included noncontingent reinforcement (NCR), NCR and differential reinforcement of alternative behavior (DRA), and NCR‐and‐DRA with punishment. During the NCR‐and‐DRA with punishment phase, four to five potential punishers were evaluated using a multielement design. Dependent measures included the target problem behavior, appropriate item engagement, and emotional responding. For all participants, NCR‐and‐DRA was not effective and punishment was necessary. However, the most effective punisher identified in the context of NCR‐and‐DRA differed across participants.